Application of Warm Compresses in Patients with Dengue Hemorrhagic Fever (DHF) with Hyperthermia in Room Cendana 3, Kardinah Regional General Hospital, Tegal City - Azizah N, Sopiani; Setyo Dwi Andhini, Citra (INDOGENIUS, 2025)
Background & Objective: Dengue Hemorrhagic Fever (DHF), medically known as Dengue Hemorrhagic Fever/DHF, is an infectious disease caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. It is characterized by sudden fever lasting 2 to 7 days without a clear cause, weakness/fatigue, restlessness, abdominal pain, accompanied by skin bleeding manifestations such as petechiae, ecchymoses, or rashes (petechiae). A warm compress is a procedure using a cloth, washcloth, or towel soaked in warm water, then applied to specific body parts to provide comfort and lower body temperature. The purpose of this study is to describe cases of Dengue Hemorrhagic Fever in detail and depth. Method: This study was conducted using a qualitative descriptive method with a case study approach. The study was conducted at Kardinah General Hospital in Tegal City on patients with Dengue Hemorrhagic Fever/DHF on December 10, 2024. Result: The application of warm compresses as a non-pharmacological therapy was effective in reducing the body temperature of patients. Warm compresses were proven to have a positive effect in managing fever caused by DHF, resulting in a decrease in patients' fever after treatment was administered. Conclusion: It is recommended that research in the field of nursing, particularly pediatric nursing for patients with DHF, be further enhanced to improve the quality of care and provide more specific and targeted nursing interventions.